Feeding versus falling: the growth and collapse of molecular clouds in a turbulent interstellar medium - Ibáñez Mejía, Juan Camilo; Mac Low, Mordecai-Mark; Klessen, Ralf S.; Baczynski, Christian (The astrophysical journal, 2017)
In order to understand the origin of observed molecular cloud (MC) properties, it is critical to understand how clouds interact with their environments during their formation, growth, and collapse. It has been suggested that accretion-driven turbulence can maintain clouds in a highly turbulent state, preventing runaway collapse and explaining the observed non-thermal velocity dispersions. We present 3D, adaptive-mesh-refinement, magnetohydrodynamical simulations of a kiloparsec-scale, stratified, supernova-driven, self-gravitating, interstellar medium (ISM), including diffuse heating and radiative cooling. These simulations model the formation and evolution of a MC population in the turbulent ISM. We use zoom-in techniques to focus on the dynamics of the mass accretion and its history for individual MCs. We find that mass accretion onto MCs proceeds as a combination of turbulent flow and near free-fall accretion of a gravitationally bound envelope. Nearby supernova explosions have a dual role, compressing the envelope and increasing mass accretion rates, but also disrupting parts of the envelope and eroding mass from the cloud’s surface. It appears that the inflow rate of kinetic energy onto clouds from supernova explosions is insufficient to explain the net rate of change of the cloud kinetic energy. In the absence of self-consistent star formation, the conversion of gravitational potential into kinetic energy during contraction seems to be the main driver of non-thermal motions within clouds. We conclude that although clouds interact strongly with their environments, bound clouds are always in a state of gravitational contraction, close to runaway, and their properties are a natural result of this collapse.
Gesehen am 10.10.2018